FRI0470 A phase 2 study of safety and efficacy of lenabasum (JBT-101), a cannabinoid receptor type 2 agonist, in refractory skin-predominant dermatomyositis. (12th June 2018) - Werth, V.P.; Hejazi, E.; Pena, S.M.; Haber, J.S.; Okawa, J.; Feng, R.; Gabre, K.; Concha, J.S.; Cornwall, C.; Dgetluck, N.; Constantine, S.; White, B.
Abstract : Background: Effective treatment options are limited for refractory skin disease in dermatomyositis (DM). Lenabasum is a non-immunosuppressive, synthetic, oral preferential CB2 agonist that triggers resolution of innate immune responses and reduces cytokine production by PBMC from DM patients. Objectives: The purpose of this study was to test safety and efficacy of lenabasum (aka JBT-101, anabasum) in DM subjects with refractory, moderate-to-severely active skin disease. Methods: A double-blind, randomised placebo-controlled 16 week Phase 2 trial (JBT101-DM-001; NCT02466243 ) enrolled adults with documented DM and a Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) activity score ≥14, minimal active muscle involvement and failure or intolerance to hydroxychloroquine and stable DM medications including immunosuppressants. Subjects received 2 escalating dose levels of lenabasum (20 mg QD X 4 weeks, then 20 mg BID X 8 weeks) or PBO X 12 weeks. Subjects were followed off study drug X 4 weeks. Safety and efficacy outcomes were assessed from Day 1 through end of study at Week 16. The primary efficacy objective was to assess efficacy of lenabasum using CDASI activity score. Results: 11 adults each received lenabasum and PBO (n=22). Demographic and disease characteristics were similar in both cohorts. Both cohorts had mean CDASI activity scores in the severe range 33–35 despite immunosuppressants (19/22 subjects). Lenabasum subjects had clinically meaningful improvement in CDASI activity scores with mean reduction ≥5 points at all visits after 4 weeks. Improvement had statistical significance at end of study (figure 1, p=0.02, 2-sided MMRM) that first became apparent after 4 weeks. Lenabasum provided greater improvement than placebo in CDASI damage index, patient-reported global skin disease and overall disease assessments, skin symptoms including photosensitivity and itch, fatigue, sleep, pain interference with activities, pain, and physical function (examples in figure 1). Improvements in secondary efficacy outcomes reached statistical significance (p≤0.1, 1-sided MMRM) at multiple visits after week 4 (figure 1). There were no serious, severe or unexpected adverse events (AEs) related to lenabasum. Tolerability of lenabasum was excellent with no study drop-outs. Subjects in the lenabasum cohort had numerically more mild AEs than placebo subjects (29 vs. 19) and fewer moderate AEs (4 vs. 7). AEs in ≥3 subjects in any cohort were diarrhoea, dizziness (lightheadedness), fatigue and dry mouth. Conclusions: Lenabasum demonstrated consistent evidence of clinical benefit across multiple efficacy outcomes and had acceptable safety and tolerability in this Phase 2 trial in refractory skin disease in DM. Further evaluation of lenabasum in the treatment of DM is warranted. Disclosure of Interest: V. Werth Consultant for: Corbus Pharmaceuticals, Inc., E. Hejazi: None declared, S. Pena: None declared, J. Haber: None declared, J. Okawa: None declared, R. Feng: None declared, K. Gabre: None declared, J. Concha: None declared, C. Cornwall Employee of: Corbus Pharmaceuticals, Inc., N. Dgetluck Employee of: Corbus Pharmaceuticals, Inc., S. Constantine Employee of: Corbus Pharmaceuticals, Inc., B. White Employee of: Corbus Pharmaceuticals, Inc.